Think Twice Before Running! Bank Runs and Cognitive Abilities - Hubert János Kiss; Ismael Rodriguez-Lara; Alfonso Rosa-García (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
We assess the impact of cognitive abilities on withdrawal decisions in a bank-run game. In our setup, depositors choose sequentially between withdrawing or keeping their funds deposited in a common bank. They may observe previous decisions depending on the information structure. Theoretically, the last depositor in the sequence of decisions has a dominant strategy and should always keep the funds deposited, regardless of what she observes (if anything). Recognizing the dominant strategy, however, is not always straightforward. If there exists strategic uncertainty (e.g., the last depositor has no information about predecessors' decisions) the identification of the dominant strategy requires harder thinking than when there is not strategic uncertainty (e.g., the last depositor is informed about all previous decisions). We find that cognitive abilities, as measured by the Cognitive Reflection Test (CRT), predict withdrawals in the presence of strategic uncertainty (participants with higher abilities tend to identify the dominant strategy more easily) but the CRT does not predict behavior when there is no strategic uncertainty.
Keywords: C91; D03; D8; G02; J16; 330; bank runs; coordination game; observability of actions; cognitive abilities; strategic uncertainty